2019
DOI: 10.1371/journal.pone.0202453
|View full text |Cite
|
Sign up to set email alerts
|

A prospective, observational study on conversion of clinically isolated syndrome to multiple sclerosis during 4-year period (MS NEO study) in Taiwan

Abstract: Importance CIS to MS conversion rates vary depending on population cohorts, initial manifestations, and durations of follow-up. Objective To investigate conversion rate of patients from CIS to MS and the prognostic significance of demographic and clinical variables in Taiwanese population. Design Nationwide, prospective, multi-centric, observational study from November 2008 to November 2014 with 4 years follow-up. Setting … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…8 This issue becomes even more confusing when presented with findings from a 4-year prospective study following 153 clinically isolated syndrome cases. In contrast with previous studies, the authors found that being underweight was a significant predictor of conversion from a clinically isolated syndrome to MS. 9 Moreover, these findings are in agreement with a Canadian case control study including 197 cases. An inverse association was observed between a high BMI and risk of MS.…”
supporting
confidence: 86%
“…8 This issue becomes even more confusing when presented with findings from a 4-year prospective study following 153 clinically isolated syndrome cases. In contrast with previous studies, the authors found that being underweight was a significant predictor of conversion from a clinically isolated syndrome to MS. 9 Moreover, these findings are in agreement with a Canadian case control study including 197 cases. An inverse association was observed between a high BMI and risk of MS.…”
supporting
confidence: 86%
“…In one of them, BMI has shown a correlation with the progression of the disease and a higher frequency of relapses but was in no correlation with the prediction of the conversion from a clinically isolated syndrome to MS. 55 In other studies it was shown that in a population of MS patients during the one year follow-up there was an increase in physical disability, but there were minimal pieces of evidence that BMI was a predictive factor for this change. 56 Taiwanese researchers have shown that the BMI values below the normal range with more than four demyelinating lesions are a strong predictor for the conversion from a clinically isolated syndrome to MS. 57 It was also confirmed that the BMI values affected the prediction of cognitive disorders in patients suffering from MS. 58 So far, in several studies, the BMI has been stu-died as a factor influencing the onset of MS. Results of this study showed that BMI affected the progression and prediction of the disease, but not the degree of physical disability of patients with MS. To prevent these undesirable effects, it is very important to emphasise that this environmental factor is suitable for modification.…”
Section: Resultsmentioning
confidence: 75%
“…DAWM was associated with individuals in the high‐risk stratum, which had to meet one of the two known high‐risk features, either modified Barkhof criteria, or the presence of more than one enhancing lesion. The modified Barkhof criteria were incorporated into the 2010 McDonald diagnostic criteria because of their strong prognostic power, 40,41 which has been confirmed in multiple studies 26,28,32,42–45 . Satisfying the modified Barkhof criteria also indicates the MRI meets the 2005 McDonald dissemination in space criteria.…”
Section: Discussionmentioning
confidence: 98%